How painting happens (and why it matters) / Martin Gayford. - Gayford, Martin, 1952- (Thames & Hudson Ltd., 2024)
Drawing on decades of conversations with practising artists Martin Gayford offers intimate insight into the practice, meaning and potential of painting.